TEACHERS AS ROLE MODELS IN NURTURING STUDENTS’ CHARACTER - Yenni Hasnah (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Abstract The aim of education is not merely dealing with the conveying of knowledge to students where the goal is focused on the pupils’ skills. Further, it ought to yield more essential aspects of their lives–character building, such as honesty, discipline, self-esteem, responsibility, respect for self and others, and trustworthiness, which in actual affect significantly the relationship with classmates, teachers, families and environments. In this case, teachers own a noble responsibility to nurture virtues on education, and being able to establish students’ attitudes. The role of teachers as models for students should be reflected through the teaching and learning process of interdisciplinary subjects. As a result, it provides them with intellectual, social, emotional, and ethical development.Keywords: Teachers, Role Models, Students’ Character